Antibacterial activity of different types of snake venom from the Viperidae family against Staphylococcus aureus - Canhas, Isabela Nascimento (2017)
Toxins and venoms produced by living organisms have exhibited a variety of biological activities against microorganisms. In this study, we tested seven snake venoms from the family Viperidae for antibacterial activity and the activities of reversal of antibiotic resistance and inhibition of biofilm formation against 22 clinical isolates of Staphylococcus aureus. Bothrops moojeni venom exhibited anti staphylococcal activity with the lowest mean value of minimum inhibitory concentration (MIC). Moreover, reversal of antibiotic resistance was observed for combinations of B. moojeni venom (½ x MIC) and norfloxacin or ampicillin (both ½ x MIC) for 86.4% and 50% of the isolates, respectively. B. moojeni venom alone at ½ MIC inhibited 90% of biofilm formation, whereas in combination with ciprofloxacin, both at ½ MIC, a reduction on the NorA efflux pump activity was observed. The detection of in vitro mutants colonies of S. aureus resistant to B. moojeni venom was low and they did not survive. A phospholipase A2 was purified from the venom of B. moojeni and displayed anti-staphylococcal activity when tested alone or in combination with ciprofloxacin. The results presented here will contribute to the search for new antimicrobial agents against resistant S. aureus.